Shakespeare and the implications of paratextual attribution - Lidster, A (Associated University Presses, 2018)
In 1598, Shakespeare's name first appeared-unambiguously-on the title pages of printed playbooks, with the second editions of Richard II and Richard III, both published by Andrew Wise, and the first extant edition of Love's Labour's Lost, published by Cuthbert Burby.1 These paratextual attributions have generated considerable critical interest and are often used to suggest the increasing status of commercial drama and of Shakespeare's position as the most published professional dramatist at the end of the sixteenth century. From these brief considerations-specifically, the concentration of Wise's output, the association between Wise, George Carey, and the Chamberlain's Men, the timing of the publications and Stationers' Register entries, and the consistency in printed presentation-the Shakespearean attributions in the Wise quartos can be seen as pointing towards a patronage network that has influenced the selection and presentation of these plays in print, as well as our understanding of the relationship between published texts and wider performance repertories. While critics including Adam Hooks and Kathleen McLuskie have explored these connections, a divide is still often maintained in assessing patronage and commercial motivations; Wise's quartos help to break down this distinction, demonstrating a synergetic relationship between these influences that is especially apparent through Wise's position within London's literary landscape.5 Wise was a publisher and bookseller by trade, and throughout his entire documented career (from 1593 to 1603), he operated at the Sign of the Angel in the northeast corner of St Paul's Churchyard. The quartos published by Andrew Wise between 1597 and 1602 are particularly revealing for understanding Shakespearean publication, pointing to the existence of a patronage network that possibly informed the selection and presentation of these plays, and highlighting the interactions between dramatic and non-dramatic publications on the bookstalls.